Demoralization and death anxiety in advanced cancer. Issue 11 (20th August 2018) - An, Ekaterina; Lo, Christopher; Hales, Sarah; Zimmermann, Camilla; Rodin, Gary
Abstract: Objective: The circumstances of advanced cancer can cause considerable psychological distress, including death anxiety and demoralization. Although these states of existential distress have a negative impact on the quality of life of patients with advanced cancer, they are rarely evaluated as outcomes or targets of interventions in this population. In an effort to improve understanding of existential distress, a structural model of relationships among death anxiety, demoralization, symptom burden, and social relatedness was tested in patients with advanced cancer. Methods: A total of 307 patients with advanced cancer completed baseline measures including the Death and Dying Distress Scale, the Demoralization Scale, the modified Experiences in Close Relationships Scale, the Life Completion subscale of the Quality of Life Evaluation—Cancer scale, the Memorial Symptom Assessment Scale, and Karnofsky Performance Status. A structural equation model of protective and risk factors for demoralization and death anxiety was tested. Results: The final model had good fit (SRMR = 0.061; RMSEA = 0.077; CFI = 0.927; NNFI = 0.902) in which death anxiety was positively associated with demoralization ( β = 0.71), and demoralization was positively associated with symptom burden ( β = 0.31) and negatively associated with social relatedness ( β = −0.74). Conclusions: The findings of this study suggest that demoralization and death anxiety are closely linked in patients with advanced cancer. The contribution of both symptom burden and low social relatedness to demoralization suggests that an integrated intervention addressing both physical and psychosocial disease factors may be most effective at alleviating such states of existential distress.